“The heart above the ruins”: Miriam Waddington’s Poetry, the Spanish Civil War, and Jewish Canadian Literature - Sharpe, Emily Robins (Canadian Jewish Studies / Études juives canadiennes, 2018)
The Jewish Canadian writer Miriam Waddington returned repeatedly to the subject of the Spanish Civil War, searching for hope amid the ruins of Spanish democracy. The conflict, a prelude to World War II, inspired an outpouring of literature and volunteerism. My paper argues for Waddington’s unique poetic perspective, in which she represents the Holocaust as the Spanish Civil War’s outgrowth while highlighting the deeply personal repercussions of the war – consequences for women, for the earth, and for community. Waddington’s poetry connects women’s rights to human rights, Canadian peace to European war, and Jewish persecution to Spanish carnage.